Degenerative and inflammatory markers in the cerebrospinal fluid of multiple sclerosis patients with relapsing-remitting course of disease and after clinical isolated syndrome - Sladkova, Vladimira; Mareš, Jan; Lubenova, Blanka; Zapletalova, Jana; Stejskal, David; Hlustik, Petr; Kanovsky, Petr (Neurological research, 2011)
BACKGROUND: Literature includes evidence of initial predominance of inflammation and later development of neurodegeneration in the pathogenesis of multiple sclerosis (MS). OBJECTIVE: To search for differences in inflammatory and degenerative cerebrospinal fluid (CSF) markers between relapsing-remitting MS (RRMS) and the clinical isolated syndrome (CIS). METHODS: A total of 148 subjects were evaluated, 65 MS patients (45 RRMS and 20 CIS) and 83 controls. The evaluated parameters included albumin quotient and prealbumin, transferrin, C3 and C4 complement factors, haptoglobin, beta-2-microglobulin, orosomucoid, alpha-1-antitrypsin, apolipoprotein A-I, apolipoprotein B, cystatin C, neuron-specific enolase, tau protein, beta-amyloid, oligoclonal IgG band (OCB), and IgG quotient (QIgG). RESULTS: No differences were found in the inflammatory and degenerative CSF markers between patients with RRMS and CIS. QIgG was higher in RRMS than that in CIS but the number of OCB was higher after CIS. Cystatin C levels were significantly lower in RRMS compared to the other groups. It can be considered an indicator of the demyelination degree. Normal values of beta-amyloid were less frequent in RRMS compared to those in controls.
Keywords: Multiple Sclerosis, Relapsing-Remitting; senioři; proteiny v mozkomíšním moku; Immunoglobulins; degenerace nervu; mediátory zánětu; Predictive Value of Tests; mladiství; Middle Aged; mužské pohlaví; prediktivní hodnota testů; Adult; mladý dospělý; Nerve Degeneration; Inflammation Mediators; Demyelinating Diseases; Nerve Tissue Proteins; Young Adult; ženské pohlaví; Humans; demyelinizační nemoci; biologické markery; proteiny nervové tkáně; lidé středního věku; relabující-remitující roztroušená skleróza; imunoglobuliny; Cerebrospinal Fluid Proteins; dospělí; Biomarkers; Female; Aged; Adolescent; lidé; Male